2008
DOI: 10.1175/2008jcli1758.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Indian Ocean Dipole on Poleward Propagation of Boreal Summer Intraseasonal Oscillations

Abstract: The influence of the Indian Ocean dipole (IOD) on the poleward propagation of boreal summer intraseasonal oscillations (BSISOs) is examined using observed datasets. This study finds that coherent (incoherent) poleward propagation of precipitation anomalies from 5°S to 25°N are observed during negative (positive) IOD years. Disorganized poleward propagation of BSISO in the south equatorial Indian Ocean is observed during positive IOD years. The rationale behind such an anomaly in the poleward propagation of BSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…It seems however that this flow anomaly over the Arabian Sea remains quite poorly correlated to DMI (r *0.20) resulting in little overall influence of the IOD on the Indian rainfall. Another possible reason for the weak correlations may be due to the asymmetry in the respective impact of the positive and negative IODs on summer monsoon intraseasonal Oscillations over India (Ajayamohan et al 2008). Finally, results are relatively similar when considering the entire South Asian monsoon over land and ocean (ISAS), with slightly weaker biases (Fig.…”
Section: Indian Summer Monsoonmentioning
confidence: 79%
“…It seems however that this flow anomaly over the Arabian Sea remains quite poorly correlated to DMI (r *0.20) resulting in little overall influence of the IOD on the Indian rainfall. Another possible reason for the weak correlations may be due to the asymmetry in the respective impact of the positive and negative IODs on summer monsoon intraseasonal Oscillations over India (Ajayamohan et al 2008). Finally, results are relatively similar when considering the entire South Asian monsoon over land and ocean (ISAS), with slightly weaker biases (Fig.…”
Section: Indian Summer Monsoonmentioning
confidence: 79%
“…The meridional vertical structure of composite MISO in both the periods (1979–1988 and 2001–2010) is shown in Figure . The vertical structure of the composite MISO is created based on the methodology adopted by previous studies [ Jiang et al ., ; Ajayamohan et al ., ]. First, a latitude time diagram of positive MISO precipitation anomalies averaged over 70°E–95°E is plotted for each year (figure not shown).…”
Section: Observational Resultsmentioning
confidence: 99%
“…A phase composite of the MISO is computed at each reference latitude over which the maximum positive precipitation anomalies occur. Since these composite structures bear a close resemblance, we further made a composite of these structures with respect to the maximum convection center [ Jiang et al ., ; Ajayamohan et al ., ]. From Figure , clearly, during the recent decade, the amplitude of vorticity, divergence, specific humidity, and vertical velocity have strengthened to the north of the convection.…”
Section: Observational Resultsmentioning
confidence: 99%
“…Studies show that the IOZM is most significantly correlated with the local Hadley cell, which influences the Asian monsoons (Slingo and Annamalai 2000). The IOZM has been noted to influence MJO activity as well (Rao et al 2007;Ajayamohan et al 2008). Kug et al (2009) showed that the high-frequency atmospheric variability in the Indian Ocean is modulated by IOZM events and that MJO and synoptic eddies become significantly energetic during negative IOZM events.…”
Section: B Mjo-monsoon Relationsmentioning
confidence: 99%